2008
DOI: 10.1016/j.juro.2007.11.076
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Flexible Ureterorenoscopy and Holmium:YAG Lithotripsy for Intrarenal Stones in Anticoagulated Cases

Abstract: When necessary, ureterorenoscopy and Ho:YAG lithotripsy can be performed safely and efficaciously for renal calculi in patients on anticoagulation therapy without the need for perioperative manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 13 publications
1
55
0
10
Order By: Relevance
“…This is because endoscopic procedures with (17). Thus, URS and HLL may be the only option for these patients with coagulopathies since they are often poor candidates for SWL or PCNL due to hemorrhagic and thromboembolic complications (10,13). In the present study, 6 out of 9 patients (patients 1, 2, 4, 5, 8, 9) in Group I undergoing URS and laser lithotripsy had significant stone burden (Table-1).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…This is because endoscopic procedures with (17). Thus, URS and HLL may be the only option for these patients with coagulopathies since they are often poor candidates for SWL or PCNL due to hemorrhagic and thromboembolic complications (10,13). In the present study, 6 out of 9 patients (patients 1, 2, 4, 5, 8, 9) in Group I undergoing URS and laser lithotripsy had significant stone burden (Table-1).…”
Section: Discussionmentioning
confidence: 59%
“…Another patient (4%) developed DVT with pulmonary embolism on POD 4 requiring IVC filter since he had developed hemorrhage when anticoagulation was initiated (2). Furthermore, the expense of bridging therapy (with low molecular weight heparin or intravenous heparin) is considerable (10). Therefore, the present study expands the indications for URS in patients with coagulopathies to those who are traditionally treated with PCNL with reversal of their anti-coagulation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Turna et al demonstrated the safety of this procedure in anticoagulated cases. 20 Our study, though limited, proved the effectiveness of flexible ureteroscopy with Holmium laser for managing calyceal and diverticular calculi. As with any new procedure there was a learning curve, but successfully cleared calculi in 70.55% cases after one or two sessions without any residue.…”
Section: Discussionmentioning
confidence: 59%